2003
DOI: 10.1002/pmic.200300547
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of heat shock protein 70 as a candidate target for enhancing apoptosis induced by farnesyl transferase inhibitor

Abstract: Farnesyl transferase inhibitors (FTIs) are novel antitumor drugs with clinical activity. FTIs inhibit cell growth not only by preventing direct Ras farnesylation but also through a Ras-independent pathway. Proteomics has been shown to be a powerful tool to monitor and analyze molecular networks and fluxes within the living cells and to identify the proteins that participate in these networks upon perturbation of the cellular environment. To observe early and dynamic protein changes in the cellular response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 24 publications
2
21
0
1
Order By: Relevance
“…25,26 All these antiapoptotic roles suggest that Hsp70 may be involved in resistance to imatinib, similarly to its participation in other forms of drug resistance. 21,27,28 In the present study, we confirm that the K562-r cells resistant to imatinib are also resistant to nilotinib, the novel tyrosine kinase inhibitor (AMN107) that was initially developed as a potent Bcr-Abl inhibitor based on the molecular structure of imatinib. We detect by Western blotting that Hsp70 is overexpressed in K562-r cells, as compared to their imatinib-sensitive counterparts.…”
Section: Introductionsupporting
confidence: 60%
“…25,26 All these antiapoptotic roles suggest that Hsp70 may be involved in resistance to imatinib, similarly to its participation in other forms of drug resistance. 21,27,28 In the present study, we confirm that the K562-r cells resistant to imatinib are also resistant to nilotinib, the novel tyrosine kinase inhibitor (AMN107) that was initially developed as a potent Bcr-Abl inhibitor based on the molecular structure of imatinib. We detect by Western blotting that Hsp70 is overexpressed in K562-r cells, as compared to their imatinib-sensitive counterparts.…”
Section: Introductionsupporting
confidence: 60%
“…It has been previously reported that up-regulation of hsp70 can protect ovarian cancer cells from FTI-induced apoptosis (25). In addition, blockade of hsp27 expression has been shown to overcome PS-341 resistance in lymphoma cell lines (26,27).…”
Section: Microarray Analysismentioning
confidence: 99%
“…Inhibition of the PI-3 kinase/Aktmediated cell survival and adhesion pathway by FTIs has been shown to play a role in the induction of apoptosis (9). Heat shock protein 70 may also be a target for induction of apoptosis by FTIs as well (10,11).…”
Section: Introductionmentioning
confidence: 99%